Thermal time methods and sowing dates in phyllochron determination in wheat cultivars - Rosa, Hamilton Telles; Walter, Lidiane Cristine; Streck, Nereu Augusto; Alberto, Cleber Maus (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the effect of degree-days and sowing dates calculation methods on phyllochron determination in wheat (Triticum aestivum) cultivars. A three-year field experiment with 13 sowing dates was conducted for three years (2005–2007) in Santa Maria, RS, Brazil, using six wheat cultivars: BRS Louro, CEP 52, CEP 51, BRS 177, Nova Era and BRS Tarumã. The phyllochron (°C day leaf-1) was estimated by the inverse of the slope of the linear regression of the Haun stage against the accumulated thermal time calculated using six methods. The thermal time calculation method affects wheat phyllochron estimates. The use of the three cardinal temperatures for leaf emission and cardinal temperatures compared to the minimum and maximum air temperatures improves the precision of the vegetative development simulation of this crop, in comparison to the other methods. The phyllochron varies with wheat cultivar and sowing date, and early cultivars (BRS Louro and CEP 51) have lower phyllochron than late cultivars (Nova Era and BRS Tarumã). The phyllochron is greater in sowings carried out during fall and winter than in the ones carried out during spring and summer.